SIMULTANEOUS ESTIMATION AND METHOD DEVELOPMENT FOR L-CARNITINE AND METFORMIN IN HUMAN PLASMA USING LC-MS/MS - BINO, JAMES D TERISH; Kannappan; Jith, Sasi; Kumar, Suresh (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objectives: The objective was to develop a robust simultaneous method for quantifying L-Carnitine and metformin using liquid chromatography mass spectrometer (LCMSMS). Methods: LCMSMS method was developed considering its selectivity, sensitivity, and accuracy. Blank correction method was followed as L-Carnitine is found endogenously. Range was selected based on the Normal value for L-Carnitine and maximum concentration for metformin. Results: Rugged simultaneous method using ultra flow LC mass spectrometer for the estimation of L-Carnitine and metformin, in human plasma with low limit of quantification and upper limit of quantification of 2.289 Î¼g/mL and 33.675 Î¼g/mL for L-Carnitine, 43.483 ng/ml and 639.450 ng/ml for metformin, respectively, was developed which can be used for therapeutic drug monitoring and as a prognostic tool for Type 2 diabetes mellitus (T2DM). Extraction was optimized using Protein precipitation (PP) in which sample clean-up was simple, and recovery was consistent. Linearity was checked and found to be within acceptance criteria with 1/Ã—2 as the weighing factor. As L-Carnitine is present endogenously blank correction was carried by injecting blank six times and calculated for normalization. As the extraction is by simple PP internal standard was not used, and method is meeting the criteria for validation using LCMSMS. Conclusion: Hence, considering L-Carnitine as the biomarker for T2DM and metformin as the drug for treatment, a simultaneous method was developed which can be validated as per regulatory requirements and can be verified for the applicability of the method as a therapeutic drug monitoring and prognostic tool. Keywords: L-Carnitine, Metformin, Type 2 diabetes, Liquid chromatography mass spectrometer.